2004
DOI: 10.1002/mrc.1483
|View full text |Cite
|
Sign up to set email alerts
|

Non‐empirical calculations of NMR indirect carbon–carbon coupling constants. Part 10—Carbocages

Abstract: A comprehensive theoretical study of nine classical caged polycycloalkanes (tetrahedrane, prismane, homoprismane, quadricyclane, cubane, pentaprismane, hexaprismane, adamantane and diamantane) was carried out with special focus on the structural behavior of their J(C,C) values calculated at the SOPPA level. The structural behavior of J(C,C) in small carbocages is dominated by steric strain whereas in medium-sized polycycloalkanes the J(C,C) values show no marked peculiarities and follow several well-defined st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 193 publications
4
18
1
Order By: Relevance
“…113 The same effect was manifested later for carbon-carbon bonds (n - In the pioneering paper by Perlin and Casu, 116 it was found that the axial one-bond carbon-hydrogen couplings in the six-membered saturated heterocycles are dramatically smaller (by ca 10 Hz) than those of the equatorial C-H bonds adjacent to either oxygen or nitrogen of the ring, and this was attributed 117 to the hyperconjugative n -Ł C -H interaction involving the antibonding orbital of the axial C-H bond and the heteroatom lone pair (see also reviews 118 and references cited therein). In the same manner, the smaller value of 1 (C,H), the numerical magnitude of the Perlin effect experimentally measured for cyclohexane of ca 4 Hz 93 is well reproduced in the present study by both SOPPA and SOPPA(CCSD) calculations, being ca 5-7 Hz in cyclobutane (2), cyclopentane (3) and cyclohexane (4) and much less (ca 1-2 Hz) in cycloheptane (5) and cyclooctane (6).…”
Section: Carbon-hydrogen Couplings In Monocycloalkanessupporting
confidence: 88%
See 4 more Smart Citations
“…113 The same effect was manifested later for carbon-carbon bonds (n - In the pioneering paper by Perlin and Casu, 116 it was found that the axial one-bond carbon-hydrogen couplings in the six-membered saturated heterocycles are dramatically smaller (by ca 10 Hz) than those of the equatorial C-H bonds adjacent to either oxygen or nitrogen of the ring, and this was attributed 117 to the hyperconjugative n -Ł C -H interaction involving the antibonding orbital of the axial C-H bond and the heteroatom lone pair (see also reviews 118 and references cited therein). In the same manner, the smaller value of 1 (C,H), the numerical magnitude of the Perlin effect experimentally measured for cyclohexane of ca 4 Hz 93 is well reproduced in the present study by both SOPPA and SOPPA(CCSD) calculations, being ca 5-7 Hz in cyclobutane (2), cyclopentane (3) and cyclohexane (4) and much less (ca 1-2 Hz) in cycloheptane (5) and cyclooctane (6).…”
Section: Carbon-hydrogen Couplings In Monocycloalkanessupporting
confidence: 88%
“…111 The only welldefined example of the pronounced medium effects in the values of J(C,C) was found in acetylene. The latter constant was measured recently with ultrahigh experimental accuracy by Chertkov in acetone-d 6 liquid phase (166.010 š 0.004 Hz), cited as a personal communication by Wigglesworth et al,32d and also by Jackowski et al 99 in dilute xenon gaseous solution (174.78 š 0.02 Hz). The former (166.01 Hz) seems to be surprisingly small and the latter (174.78 Hz) seems to be surprisingly large compared with the originally reported value of 171.5 Hz measured in CCl 4 liquid phase.…”
Section: Effects Of Electronic Correlation Vibrational Averaging Andmentioning
confidence: 82%
See 3 more Smart Citations